Advancements in Bone Cements: A Review of Ceramic, Glass and Glass-Ceramic Materials and Their Reinforcements for Orthopedic Applications - Pallabi Roy; Poulomi Mukherjee; Sumana Ghosh (Chemical and Materials Sciences: Developments and Innovations Vol. 6, 2024)
Ceramics, glasses and glass-ceramics have now been accepted as viable biomaterials. Injectable bioactive, biodegradable, mechanically strong and fracture-resistant bone cements are of considerable interest. Therefore, various types of bone cement have been developing having high strength, fracture resistance properties and bioactivity for biomedical applications. Recently, research has been envisaged to improve the performance of existing bone cements. Different bioactive composite bone cements have been prepared by reinforcing certain reinforcing materials such as alumina, toughened zirconia and hydroxyapatite ceramics into ceramic, glass and glass-ceramic matrix. Recently, improved biodegradable and engineered bone cement materials have been prepared by using various novel methods. The current paper is focused on ceramic, glass and glass-ceramic-based bone cements and their probable orthopaedic applications.